2014
DOI: 10.3791/51168
|View full text |Cite
|
Sign up to set email alerts
|

Production of RNA for Transcriptomic Analysis from Mouse Spinal Cord Motor Neuron Cell Bodies by Laser Capture Microdissection

Abstract: Preparation of high-quality RNA from cells of interest is critical to precise and meaningful analysis of transcriptional differences among cell types or between the same cell type in health and disease or following pharmacologic treatments. In the spinal cord, such preparation from motor neurons, the target of interest in many neurologic and neurodegenerative diseases, is complicated by the fact that motor neurons represent <10% of the total cell population. Laser capture microdissection (LMD) has been develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…constructed the expression profiling of motor neurons in mouse spinal cord by LCM and microarray. This study prompts our understanding of transcriptional changes in spinal cord motor neurons during neurogenic and neurodegenerative diseases (Bandyopadhyay et al 2014 ). More examples of down-stream utilization of LCM are overviewed elsewhere (Datta et al 2015 ).…”
Section: Technologies Based On Isolation Through Microdissection or P...supporting
confidence: 55%
“…constructed the expression profiling of motor neurons in mouse spinal cord by LCM and microarray. This study prompts our understanding of transcriptional changes in spinal cord motor neurons during neurogenic and neurodegenerative diseases (Bandyopadhyay et al 2014 ). More examples of down-stream utilization of LCM are overviewed elsewhere (Datta et al 2015 ).…”
Section: Technologies Based On Isolation Through Microdissection or P...supporting
confidence: 55%
“…For example, precise spatial transcriptomic profiling of mouse motor neurons and human postmortem tissues was conducted using LCM coupled with smart-seq2. The study demonstrated that scRNA-seq was feasible with a 62% success rate by LCM-seq, exhibiting considerable facility in different circumstances [47,50]. Moreover, another team proposed geographical position sequencing (GEO-seq) [51,52], which allowed profiling of whole transcriptomes from a small number of cells while preserving their native spatial locations by utilizing an identified list of key genes (zip-code genes) to map cells back to their origins (Figure 2B).…”
Section: Lcm-based Approachesmentioning
confidence: 99%
“…Instead, tweaking subtype-specific effector molecules may be a powerful strategy to regenerate functional MNs in fully developed adults. The identification of additional effectors can be achieved in two ways: (i) oriented investigation of downstream targets of known intrinsic regulators such as LIM and/or HOX proteins for example and (ii) unbiased screenings combining, viral retrograde tracing (Stepien et al, 2010 ; Tripodi et al, 2011 ), laser capture micro-dissection (Bandyopadhyay et al, 2014 ) and RNA sequencing (Enjin et al, 2010 ). Such approaches would indubitably unveil new regulators and effectors of SpMN subtype specification.…”
Section: Generation Of Spinal Motor Neuronsmentioning
confidence: 99%